Duckweed: The hidden treasure - Jha, Sasinath; Pokharel (Bhattarai), Bindu (Nepalese Journal of Biosciences, 2015)
In recent years, the tiny aquatic angiospermic plants ‘duckweeds’ have become prominent because they provide high protein animal feed, organic fertilizer, bio-fuel; control mosquitoes; and, have great applicability in wastewater purification, toxicity testing, and in basic research and evolutionary model system. In the aforesaid context, this presentation deals in brief with general characteristics, distribution, environmental requirements, aquaculture, and some uses of duckweeds.